Menjadikan Perempuan Papua Yang Berdaya (Study Analisa GESI Terhadap Perempuan Papua Sebagai Agen Perdamaian dan Kohesi Sosial) - Anil Dawan; Andina Mega Larasati (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2022)
This article aims to describe the results of the GESI analysis. The method used is the GESI (Gender Equality and Social Inclusion) assessment. From the results of the GESI analysis it was found that the role of Papuan women in religious activities was quite high, both in routine religious meetings and involvement in planning religious activity programs and peace education. However, from 4 (four types of involvement) it was found that women's role was only in the "listening position". These results prove that there is an imbalance of systemic decision-making power in society. Thus, capacity building for Papuan women and religious, customary, community and government institutions is needed so that women's roles can be maximized in peace and social cohesion.